The Relationship Between Gadget Usage Patterns and The Incidence of Asthenopia Among Junior High School Students in Mataram - Savitri, Komang Dewi; Geriputri, Ni Nyoman; Andari, Marie Yuni (Jurnal Biologi Tropis, 2026)
Gadget use among junior high school students continues to rise, clearly contributing to asthenopia through extended exposure and inadequate self-regulation. This study directly assesses the impact of gadget use on asthenopia among junior high school students in Mataram City. Observational analytical research using a cross-sectional design enrolled 118 participants via simple random sampling. Data collected from gadget-use questionnaires and the Visual Fatigue Index (VFI) were analyzed with chi-square tests and binary logistic regression. Results confirmed that 57.6% of participants demonstrated poor usage habits, while 31.4% experienced asthenopia. No statistically significant relationship was found between overall gadget use and asthenopia (p = 0.785). Nonetheless, device use exceeding 2 hours emerged as the primary factor linked with asthenopia. In summary, poor gadget use is widespread, and prolonged use increases the risk of asthenopia, although this study did not find a significant overall link. Eye itching clearly dominated reported symptoms. To advance understanding and support student well-being, future research must employ objective measures of visual function and develop effective strategies for healthier use of devices.